INTESTINAL ORGANOIDS FOR STUDYING THE EFFECTS OF LOW-DOSE/LOW-DOSE-RATE RADIATION. Issue 13 (9th September 2022) - Fujimichi, Yuki; Otsuka, Kensuke; Tomita, Masanori; Iwasaki, Toshiyasu
Abstract: Radiation response differs depending on the dose and dose rate in intestinal stem cells; however, the underlying mechanisms are not clear. To understand the effects of low-dose and low-dose-rate radiation, the authors established an organoid system that mimics the in vivo environment and sporadic low-dose-rate irradiation conditions in vitro . Organoid-forming potential and the number of stem cells in the organoids derived from 1 Gy-irradiated cells were lower than those from non-irradiated cells; however, the difference was not significant, although 1 Gy-irradiated stem cells exhibited significant growth disadvantage in the mixed-organoid with non-irradiated and irradiated stem cells. Furthermore, the authors irradiated a cell with X-ray microbeams and performed time-lapse observations and found that irradiated cells did not remain in the organoid. These results suggest that radiation-induced stem cell competition can occur in intestinal organoids and contribute to a low risk of cancers at low-dose-rate exposures.